Effect of fermented rice bran and chitosan on duck livestock productivity - Sahara, Eli; Sandi, Sofia; Sari, Meisji Liana; Mushawwir, Andi (Journal of Advanced Veterinary Research, 2025)
This study examined how adding fermented rice bran and chitosan to duck diets affects hematological profiles, blood cholesterol, egg cholesterol, enzyme activity, and fatty acid content in duck meat and eggs. The research employed an experimental design with a Completely Randomized Design (CRD) with four treatments: R0 = 45% corn + 35% concentrate + 20% unfermented rice bran; R1 = 45% corn + 35% concentrate + 20% fermented rice bran; R2 = 45% corn + 35% concentrate + 19.5% fermented rice bran + 0.5% chitosan; R3 = 45% corn + 35% concentrate + 17.5% fermented rice bran + 2.5% chitosan, with five replications. The results showed that fermented rice bran and chitosan increased hematocrit levels, hemoglobin, erythrocyte, and leukocyte counts. They also affected blood glucose and cholesterol levels, meat cholesterol, and eggs from Tegal ducks. Some treatments significantly reduced cholesterol. Additionally, treatments influenced enzyme activity: R3 exhibited increased amylase and protease activity and decreased lipase activity. Blood glucose levels decreased in treatments R2 and R3, and blood cholesterol levels were reduced in R2, with specific treatments showing significant reductions. The combined use of fermented rice bran and chitosan impacted the fatty acid composition of duck eggs and meat. Overall, this study demonstrates that incorporating fermented rice bran and chitosan into duck diets can improve health parameters and enhance the quality of duck products.